THE LEGAL CONTROVERSIES AND DISPUTES OVER THE MEANING OF JUSTICE IN CONCILIATORY POLICY IN THE LABOR COURT - A. de Vasconcellos, Marciele (2022)
Conciliation comprises an alternative way of settling labor cases that accompanies the emergence of Labor Justice in Brazil. Recently, labor conciliation has undergone a process of change that is part of the development of the "National Policy for adequate treatment of conflicts of interest" of the National Council of Justice (CNJ), and the adoption of this judicial policy is the target of controversy in the labor legal community. The present article looks into the moral content of the disputes about the meanings of labor conciliation, from the analysis of the normative repertoires mobilized by the speakers of a public hearing promoted by the CNJ in 2016, which aimed to elaborate a regulation proper to the Labor Justice. With this, we seek to demonstrate that these repertoires compose a moral grammar that has as justification principles, on the one hand, the defense of worker protection in the effectiveness of social rights in the agreements, and on the other hand, the humanization of the judiciary having as normative support the ideals of harmony and empowerment of the parties in conflict resolution.